Consensus guidelines on the optimal management in interventional EUS procedures: results from the Asian EUS group RAND/UCLA expert panel. Issue 7 (20th February 2018) - Teoh, Anthony Y B; Dhir, Vinay; Kida, Mitsuhiro; Yasuda, Ichiro; Jin, Zhen Dong; Seo, Dong Wan; Almadi, Majid; Ang, Tiing Leong; Hara, Kazuo; Hilmi, Ida; Itoi, Takao; Lakhtakia, Sundeep; et al.
Abstract : Objectives: Interventional endoscopic ultrasonography (EUS) procedures are gaining popularity and the most commonly performed procedures include EUS-guided drainage of pancreatic pseudocyst, EUS-guided biliary drainage, EUS-guided pancreatic duct drainage and EUS-guided celiac plexus ablation. The aim of this paper is to formulate a set of practice guidelines addressing various aspects of the above procedures. Methods: Formulation of the guidelines was based on the best scientific evidence available. The RAND/UCLA appropriateness methodology (RAM) was used. Panellists recruited comprised experts in surgery, interventional EUS, interventional radiology and oncology from 11 countries. Between June 2014 and October 2016, the panellists met in meetings to discuss and vote on the clinical scenarios for each of the interventional EUS procedures in question. Results: A total of 15 statements on EUS-guided drainage of pancreatic pseudocyst, 15 statements on EUS-guided biliary drainage, 12 statements on EUS-guided pancreatic duct drainage and 14 statements on EUS-guided celiac plexus ablation were formulated. The statements addressed the indications for the procedures, technical aspects, pre- and post-procedural management, management of complications, and competency and training in the procedures. All statements except one were found to be appropriate. Randomised studies to address clinical questions in a number of aspects of the procedures are urgently required. Conclusions: The current guidelines on interventional EUS procedures are the first published by an endoscopic society. These guidelines provide an in-depth review of the current evidence and standardise the management of the procedures.